Analisis kinerja routing OSPF dan EIGRP dengan teknik redistribution - Catur Budi Waluyo (SENATIK STT Adisutjipto, 2020)
As the rapid development of technology, the demand to increase the network performance becomes higher. One of the parameters of a higher network performance is the increase of data rate by determining the faster and the best way for data delivery in any network. One method was used to determine that way dynamically by using OSPF and EIGRP protocol routing.  Throughput, delay, jitter, packet loss, and speed performance were counted in this research. Based on the simulation using tracer packet software, the throughput was 45.75 bps, the delay was 5.91 ms, the jitter was 1.477 ms, and the loss packet was 0%. While the value of COST by data packet delivery in OSPF area was 781.25 kbps and the metric value of data packet delivery in EIGRP area was 20 kbps. With a good QoS value, the OSPF and EIGRP routing can be implemented for this network topology.